TINGKAT PERSEPSI LANSIA TENTANG PANDEMI COVID - Nurfarida Deliani; Anggi Fitria; Ahmad Putra (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2023)
.Coronavirus is a collection of viruses that infect the respiratory system. In most cases, this virus only causes mild respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). Corona virus infection called COVID-19 (Corona Virus Disease 2019) was first discovered in the city of Wuhan, China at the end of December 2019. This virus spread very quickly and spread to almost all countries, including Indonesia, in just a few months. This virus attacks all walks of life, young children, teenagers and even the most dangerous attack on the elderly whose immune system is weak, this causes the perception of these elderly people to be different. In relation to these problems, the purpose of this research is to find out more deeply about adolescent perceptions of the Covid-19 pandemic based on gender. This research is a quantitative research with descriptive type. The sample of this research were 77 teenagers and parents. Sampling technique with total sampling. based on the results of the study, it was found that the perception of the elderly was in the category of 3 people (6.38%) in the very high category, 5 people (10.63%) were in the high category, 17 people (14.89%) were in the medium category, 28 people (38.29%) were in the low category and 24 people (29.78%) were in the very low category.